The Effect of Brushed Salam Leaf on the Reduction of High Blood Pressure in Hypertension Patients - Kristina L. Silalahi; Novelia Nainggolan; Sugianto Simanjuntak; Ferry Anza Ginting (Global Health Science Group, 2020)
Hypertension is one of the most deadly diseases or often called silent killer what needs to get special attention, the stew laurel foliage is one alternative treatment with no side effects. The purpose of this research is to know the influence of the stew laurel foliage on reductions in high blood pressure. This is the kind of research with a quantitative research pre-experimental approaching one group pre-post test design the express and effect in a manner involving a group of the subject. This research does twice the measurement of blood pressure and blood pressure measurements conducted before and after the stew laurel foliage. The research was done in those elderly foundations to Budi medan in august by 2020. The sample is seniors who suffer from hypertension based on data from the medical record. The research has been conducted is the influence of the stew laurel foliage on the blood on the elderly 0,000 of p. The study areas are the stew leaf as regards any impact on blood pressure. It is hoped that the elderly established alternative treatment ( use stew leaf as regards hyperlens ) to prevent a recurrence.